Analyzing Meaning: An Introduction to Semantics and Pragmatics: by Paul R. Kroeger, Berlin: Language Science Press, 2018, xiv+482 pp. - Yousefi, Moslem; Mardian, Fatemeh (Australian Journal of Linguistics, 2020)
In I Analyzing Meaning i Paul Kroeger creates an interconnection between semantics and pragmatics as two evolving, capacious areas of linguistic inquiry. The chapter ends with useful topics related to expressive meaning and the properties differentiating expressive meaning from descriptive meaning, including I independence, nondisplaceability, immunity, scalability and repeatability i and I descriptive ineffability i .